Implementasi Teaching at the Right Level (TaRL) untuk Meningkatkan Literasi dan Mengatasi Kesenjangan Akademik Peserta Didik Kelas X di SMA Negeri 106 Jakarta - Setiana, Pragiwati; Siburian, Martua Ferry; Dinihari, Yulian; Alamsyah, Mashudi; Musringudin, Musringudin (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2025)
This research aims to analyze the effectiveness of the Teaching at the Right Level (TaRL) approachin strengthening literacy skills while reducing the gap in academic achievement of class X.6 students at SMANegeri 106 Jakarta. The method used is classroom action research (PTK) by integrating initial diagnosticassessments and observations of student characteristics to develop adaptive learning strategies. The researchresults show a significant increase, especially in groups of students who had not previously developed, withan average increase in achievement of 20%. In addition, group-based learning provides higher results thanindividual learning, with an average increase in grades of 18%. The role of teachers as facilitators anddiagnosers of students' literacy needs has proven to be a determining factor in the success of TaRLimplementation. However, challenges such as the integration of psychosocial support and consistency offormative assessments still need to be considered so that the impact of TaRL can be more optimal.Keywords: Teaching at the Right Level (TaRL), literacy, academic gaps, differentiated learning, seniorhigh school